The European Court of Human Rights Overwhelmed by Applications:Problems and Possible Solutions - Wolfrum, Rüdiger; Deutsch, Ulrike (Beiträge zum ausländischen öffentlichen Recht und Völkerrecht, Veröffentlichungen des Max-Planck-Instituts für ausländisches öffentliches Recht und Völkerrecht, 2009)
A contribution to the discussion on the reform of the control mechanism of the European Court of Human Rights, which is necessary to prevent a failure of the European system of human rights protection